Interferência de processos fonológicos na escrita de estudantes do ensino fundamental da cidade de Pelotas/RS - Jesus, Simone Porcino de (2021)
This work presents a study on the interference of phonological phenomena in the writing of elementary school students. Data for this research were collected in the city of Pelotas, in Rio Grande do Sul, from textual productions of 3rd and 4th grade students from two schools, one public and the other private, made available by BATALE - Banco of Written Language Acquisition Texts, through GEALE – Study Group on Written Language Acquisition of the Federal University of Pelotas. Several phonological phenomena in the students' writing were documented, however, the most frequent were: the monotongue of the [ow], the heightening of the vowel [e] and the vocalization of the postvocalic lateral [l]. The study performs a qualitative, descriptive and quantitative analysis of the data, using the theoretical-methodological assumptions of Variationist Sociolinguistics. For the development of the analysis, the linguistic factors for the phenomenon of the heightening of the vowel /e/ were considered, we will test the linguistic variables: Word class, proceeding vowel, preceding consonant and proceeding consonant. As for the phenomenon of vocalization of the lateral /l/, we tested the linguistic variables: proceeding vowel, syllable position and word class. And extralinguistic: Gender, Education and Type of school. The factors observed as influencing the appearance of the heightening of the vowel /e/ were: preceding context and proceeding context. As for the vocalization of the lateral/l/ in writing, they were: type of school, education, gender and syllable position. The results of this research showed that there are interferences of speech in students' writing through phonological phenomena. Such interferences also show that the linguistic variation that is more observed in the spoken language also occurs in the written language, mainly in the writing of students in the process of acquiring this modality.